Pendekatan MOORA dalam Rekomendasi Lulusan Terbaik Berbasis Optimalisasi Multi-Kriteria untuk Program Studi Informatika - Moch Rizal Herdiansyah; A. Sidiq Purnomo (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This research aims to overcome the obstacles in selecting the best graduates in the Informatics Study Program, Faculty of Information Technology, Mercu Buana Yogyakarta University, which has been done manually. The proposed solution is the development of a Decision Support System (SPK) based on the MOORA approach to provide recommendations that are objective, efficient, and transparent. This system utilizes five main criteria, namely Grade Point Average (GPA), study period, organizational activity, academic achievement, and non-academic achievement. Analysis was conducted on six student data, with the results of Alternatives M2, M3, and M4 having the same final score, 0.4230. However, after reviewing the GPA, M4 was selected as the best graduate because it had the highest GPA among M2 and M3. This research proves the effectiveness of the MOORA approach in supporting decision-making, although there are limitations such as the limited amount of data and the absence of testing across study programs. In the future, system development can include additional data, large-scale testing, and integration of other methods to improve accuracy and application coverage in various educational institutions.